2000
DOI: 10.1046/j.1463-1326.2000.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed release of gastrointestinal peptides in anorexia nervosa and in obesity

Abstract: Our results indicate that the release of gastrointestinal peptides is disturbed in obesity and in anorexia nervosa. These findings suggests that dysfunction of brain-gut axis may be also an important factor in the abnormal control of appetite axcept of hypothalamic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 38 publications
4
62
0
4
Order By: Relevance
“…The present study has not proven that fat-derived NPY can enter the blood stream; however, this may potentially explain the observed elevated circulating NPY levels in chronically obese subjects and T2DM patients (1). Thus, the role of adipose-derived NPY and its contribution to circulating and central regulatory action remains to be established through further in vivo studies.…”
Section: Discussionmentioning
confidence: 54%
“…The present study has not proven that fat-derived NPY can enter the blood stream; however, this may potentially explain the observed elevated circulating NPY levels in chronically obese subjects and T2DM patients (1). Thus, the role of adipose-derived NPY and its contribution to circulating and central regulatory action remains to be established through further in vivo studies.…”
Section: Discussionmentioning
confidence: 54%
“…A number of modifications in gastrointestinal function have been described in the obese, 15,16,18,19,33 which may potentially be attributable to gastrointestinal adaptation to high nutrient exposure. Whether such changes are reversible in response to energy restriction has not been investigated in detail, but is conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a large cohort found gastric emptying of both solids and liquids to be accelerated with increasing body weight, 15 whereas others have reported gastric emptying in the obese to be either similar 16 or slower, 17 when compared with lean subjects. The outcome of gut hormone measurements is also inconsistent, for example, some studies have reported lower fasting ghrelin, 15 higher fasting 18 and postprandial 16 plasma CCK, and lower postprandial PYY, 19 glucagon-like peptide-1 20 and ghrelin 21 concentrations, whereas others found no differences in PYY or glucagon-like peptide-1. 15 There is evidence that previous patterns of energy intake, in excess, in restriction and even when sustained for short periods of time, have the capacity to modify gastrointestinal function, 5,[22][23][24] and this may be of particular relevance to the inconsistent observations from studies relating to gastrointestinal function in the obese given that previous nutrient intake has not been quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of acute eating behavior incorporates a system of satiety signals that originate from the food ingested. Cholecystokinin, bombesin, gastrin-releasing peptide, amongst others, are involved in this signaling system and reach the brain via peripheral innervation or the circulation to activate their receptors in the brain (5).…”
Section: Appetite-regulating Peptidesmentioning
confidence: 99%